Developing Classifications of Laryngeal Dysplasia: The Historical Basis - Hellquist, Henrik; Ferlito, Alfio; Makitie, Antti A.; Thompson, Lester D. R.; Bishop, Justin A.; Agaimy, Abbas; Hernandez-Prera, Juan C.; Gnepp, Douglas R.; Willems, Stefan M.; Slootweg, Pieter J.; Rinaldo, Alessandra (Advances in Therapy, 2020)
During the last 60 years numerous significant attempts have been made to achieve a widely acceptable terminology and histological grading for laryngeal squamous intraepithelial lesions. While dysplasia was included in the pathology of the uterine cervix already in 1953, the term dysplasia was accepted in laryngeal pathology first after the Toronto Centennial Conference on Laryngeal Cancer in 1974. In 1963 Kleinsasser proposed a three-tier classification, and in 1971 Kambic and Lenart proposed a four-tier classification. Since then, four editions of the World Health Organisation (WHO) classification have been proposed (1978, 1991, 2005 and 2017). Several terms such as squamous intraepithelial neoplasia (SIN) and laryngeal intraepithelial neoplasia (LIN) are now being abandoned and replaced by squamous intraepithelial lesions (SIL). The essential change between the 2005 and 2017 WHO classifications is the attempt to induce a simplification from a four- to a two-tier system. The current WHO classification (2017) thus recommends the use of a two-tier system with reasonably clear histopathological criteria for the two groups: low-grade and high-grade dysplasia. Problems with interobserver variability apart, subjectivities and uncertainties remain, but to a lesser degree. Ongoing and additional molecular studies may help to clarify underlying events that will increase our understanding and possibly can facilitate our attempts to obtain an even better classification. The classification needs to be easier for the general pathologist to perform and easier for the clinician to interpret. These two objectives are equally important to provide each patient the best personalised treatment available for squamous intraepithelial lesions.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Laryngeal dysplasia; Laryngeal precancerous lesions; Laryngeal precursor lesions; WHO classification